2015
DOI: 10.7763/ijmo.2015.v5.443
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore Modeling of N1-alkyltheobromine as Histamine-H1 Receptor Antagonist

Abstract: Abstract-Previous studies worked on the evaluation a few alkylxanthine derivatives synthesized from theobromine, exhibiting micromolar activities of the compounds against histamine in vitro. The structure-activity relationships study showed that the elongation of alkyl group at N 1 of xanthine ring increased the tracheospasmolytic activity. This result opened the opportunity for alkylxanthine to be developed as antihistamine. Presently, we elucidate the mechanism of N 1 -alkylxanthine derivatives as antihistam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…They were reported to be a promising template for designing novel non-sedating H 1 R antihistaminic agents [70]. Docking studies, using AutoDock, showed that derivatives of N 1 -alkyltheobromine, which exhibited H 1 R antihistaminic activity comparable to doxepin and less CNS depressant side effects than olapatadine, interacted electrostatically and formed hydrogen bonds with residues D 3.32 , Y 3.33 , S 3.36 , T 3.37 , K 5.39 and Y 6.51 [71]. In one study, quinoline derivative (QS-15), astemizole and diclofenac sodium have been shown to interact with residues D 3.32 , W 6.48 and F 6.52 [73].…”
Section: Computational Studies On Histamine H 1 Receptor and Its Ligands 211 Structural Aspects Of Histamine H 1 Receptormentioning
confidence: 99%
“…They were reported to be a promising template for designing novel non-sedating H 1 R antihistaminic agents [70]. Docking studies, using AutoDock, showed that derivatives of N 1 -alkyltheobromine, which exhibited H 1 R antihistaminic activity comparable to doxepin and less CNS depressant side effects than olapatadine, interacted electrostatically and formed hydrogen bonds with residues D 3.32 , Y 3.33 , S 3.36 , T 3.37 , K 5.39 and Y 6.51 [71]. In one study, quinoline derivative (QS-15), astemizole and diclofenac sodium have been shown to interact with residues D 3.32 , W 6.48 and F 6.52 [73].…”
Section: Computational Studies On Histamine H 1 Receptor and Its Ligands 211 Structural Aspects Of Histamine H 1 Receptormentioning
confidence: 99%